PENGARUH PENERBITAN SURAT KETETAPAN PAJAK KURANG BAYAR, PENERBITAN SURAT TAGIHAN PAJAK , DAN PENERBITAN SURAT PENGUKUHAN PENGUSAHA KENA PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN - Dwi Kartikaningrum (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to determine the effect of the issuance of tax assessment letters underpayment, issuance of tax bills, and the issuance of inauguration letter of taxable entrepreneurs simultaneously or partially to the income tax revenue in KPP Pratama temanggung period 2012-2016.The sampling method used is a Convenience Sampling. The population in this study amounted to 60, but the sample used only 51 samples and 9 samples in outlier because it has extreme value and not normally distributed. The data used in this study is secondary data obtained from the data processing in KPP Pratama Temanggung. The analysis technique used is multiple linear regression.The result of the research proves that the issuance of tax assessment letters underpayment, issuance of letter of invoice, and issuance of inauguration letter of taxable entrepreneur simultaneously affect the income tax revenue in KPP Pratama Temanggung. Examiners partially concluded that the issuance of tax assessment letters has no effect, while the issuance of tax bills has a positive effect, and the issuance of taxable letters inauguration has a negative effect on income tax revenue in KPP Pratama Temanggung.